Impact of BAL lymphocytosis and presence of honeycombing on corticosteroid treatment effect in fibrotic hypersensitivity pneumonitis: a retrospective cohort study. Issue 4 (23rd April 2020) - De Sadeleer, Laurens J.; Hermans, Frederik; De Dycker, Els; Yserbyt, Jonas; Verschakelen, Johny A.; Verbeken, Eric K.; Verleden, Geert M.; Verleden, Stijn E.; Wuyts, Wim A.
According to a survey study conducted by Wijsenbeek et al. [1], 76% of respiratory physicians believe fibrotic hypersensitivity pneumonitis (fibrotic HP, fHP) should be treated with corticosteroids (CS) as first line treatment. However, data to support such a strategy are limited and confined to acute farmer's lung [2]. Classically, HP patients are classified according to symptom chronicity in acute and chronic HP [3]. Based on new data, however, a stratification according to the (radiological) presence of fibrosis seems more in line with prognosis [4]. In an earlier study, we demonstrated that CS treatment was only beneficial in non-fibrotic HP while CS was not effective in fHP, both in terms of survival, and decline in forced vital capacity (FVC) and diffusing capacity of the lung for carbon monoxide ( D LCO ) [5]. In the present study, we determined whether the presence of bronchoalveolar lavage lymphocytosis (BAL lymphocytosis, BALL) or honeycombing influences the treatment effect of CS in fHP patients. Low BAL lymphocytosis and presence of honeycombing predict poor outcome and absence of corticosteroid treatment effect in fibrotic hypersensitivity pneumonitis http://bit.ly/2QUl0K6